PENERAPAN PSAK No. 45 PADA ORGANISASI NON PROFIT (NPO) - Merintan Berliana Simbolon (Jurnal Web Informatika Teknologi, 2022)
This study aims to evaluate the implementation of Statement of Financial Accounting Standard (PSAK) No. 45 for non-profit organizations in Bandar Lampung in year 2012. Nonprofit entities obtain resources from sponsors who do not expect repayments or economic benefits proportional to the amount of resources provided. This study uses a sample of 22 non-profit entities in Bandar Lampung. However, for this study purpose, 4 nonprofit organizations have been selected as they met the criteria according of financial reporting standards. Data were evaluated using the focus group discussion method. The results of the study found that the PSAK No. 45 on the reporting of financial position, statement of activities, and cash flow statements have not been implemented by non-profit entities in Bandar Lampung. An exception is of one organization which prepared those as a requirement to submit a proposal for international funding.